2016
DOI: 10.4103/2347-5625.196489
|View full text |Cite
|
Sign up to set email alerts
|

Impact of symptom clusters on quality of life outcomes in patients from japan with advanced nonsmall cell lung cancers

Abstract: Objective:Identify symptom clusters based on symptoms experienced by patients with advanced nonsmall cell lung cancers (NSCLCs), and examine the relationship between the symptom clusters and impairment in everyday life and quality of life (QOL).Methods:Using the M.D. Anderson Symptom Inventory, 9 symptom items and the QOL Questionnaire (QLQ-C-30) evaluation apparatus from the European Organization for Research and Treatment of Cancer, we evaluated symptom severity, interference in daily life, and QOL. Factor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
(69 reference statements)
3
16
0
Order By: Relevance
“…The "pain" symptom group had the greatest influence on emotional functioning, but had less influence on physical and cognitive functioning. This result is consistent with several previous studies of patients with LC, which reported that the pain cluster [15] and pain [19] had strong influences on the emotional and physical functioning scales of HRQOL. The physiological response to pain can lead to anxiety and sadness, and depression or anxiety can also lead to increased pain [40].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The "pain" symptom group had the greatest influence on emotional functioning, but had less influence on physical and cognitive functioning. This result is consistent with several previous studies of patients with LC, which reported that the pain cluster [15] and pain [19] had strong influences on the emotional and physical functioning scales of HRQOL. The physiological response to pain can lead to anxiety and sadness, and depression or anxiety can also lead to increased pain [40].…”
Section: Discussionsupporting
confidence: 93%
“…Among the five HRQOL functioning domains, the "lack of energy" symptom group had the greatest influence on physical functioning (explaining 59% of the variance), role functioning (explaining 86% of the variance), and social functioning (24% of the variance). This result is in line with a previous study of patients with advanced-stage NSCLC, which reported that the fatigue/anorexia cluster had the greatest impact on physical and role functioning [15]. Most of our patients (88%) had advanced-stage NSCLC and were undergoing treatment.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations